A study of iron kinetics in normal and abnormal human subjects - French, Terence John (Division of Haematology, 2020)
The work to be presented in this thesis took pl ace while I was working as a registrar in the department of radio-isotope diagnosis at Groote Schuur Hospital. During this period, I became interested in the ferrokinetic technique for attempting to quantitate normal and abnormal erythropoietis, and the possible development of these techniques so as to allow more accurate quantitation of the data. At the time the study started, the department was offering standard ferrokinetic investigations to aid in the diagnosis of abnormal haematological states. These studies did not, I felt, provide adequate information for the referring clinician, particularly in regard to ineffective erythropoietic activity.